ABUNDANCES OF HELIUM AND OTHER ELEMENTS IN ATMOSPHERES OF CLASSICAL CEPHEIDS - Kovtyukh, V. V.; Komarov, N. S.; Depenchuk, E. A. (Одеські астрономічні публікації, 2017)
The chemical composition of three classical cepheids δ Cep, η Aql and ζ Gem, has been investigated by using model atmospheres' method. It is shown that Na and Mg are overabundant (≈+0.35 dex), C and 0 are slightly underabundant (≈ -0.20 dex) relative to the Sun. The atmospheric abundances for other elements are close to the solar composition. The low limit of helium atmospheric abundance in classical cepheids, derived from the spectrum of a physical companion of δ Cep (δ Cep-C, B7 IV, Teff =13250 K, log g=3.85, Vt=0.0 km/s), is [He/H]= -0.13. The comparison of chemical composition in the atmospheres of δ Cep cepheid and its companion obviously illustrates the variation in abundance of CNO elements during the cepheid evolution. If the primary C, 0 abundance for cepheid is solar-like (as the chemical composition of a companion corresponds to initial composition of the cepheid), then after red- supergiant phase (phase of dredge-up) we can observe the cepheid as a star being deficient in C and 0.